In Search of 'Truths': South Korean Society and the Politics of Live Streaming. (June 2023) - Kim, Ji Hyeon; Yu, Jun
Despite Castells' argument about the transformative potential of digital communication technologies for developing the networks of individuals and bringing about social and political changes, critical scholars have continued to raise vigilance against the potentially detrimental consequences of such technologies in social domains. One such issue relates to their impact on (collective) identity-making. Taking as a case study the live streaming of 2016–17 candlelight and Taegukgi rallies in South Korea, this article addresses how a digital communication technology can go further than simply permitting a large-scale mobilization and can reconfigure the meaning of participation in social movements, contributing to the emergence of what we term 'polemical identity'. We argue that this polemical identity diverges from a more hopeful perspective found in Castells' account, developing instead through the new semantics of participation that result in, and are triggered by, various practices of Otherizing. This includes searching for, and claiming, one's own 'truth' as a means of bonding with the likeminded. In this process, we illuminate how the relationship between (collective) identity, digital communication technologies, social contexts and institutional power has become more complicated.